Decorated Busts of the Antonines: New Bust Variants of Denarii from AD 138 to AD 188 (Antoninus Pius, Marcus Aurelius, Lucius Verus, Commodus, Faustina II, Lucilla) - Marinkevich, Zhenya (KOINON: The International Journal of Classical Numismatic Studies, 2021)
Modern numismatists often face a lack of comprehensive information concerning the attribution of Roman denarii with decorated busts of the rulers of the Antonine dynasty. The standard reference works on the coinage of the Antonines include RIC IIIA and RSC IIB, which catalog denarii for Antoninus Pius and Marcus Aurelius as Caesar. RSC II’s cataloging of later coinage for the Antonines is not always complete because it lacks information from those volumes of German numismatist Paul Strack on Marcus Aurelius and Commodus, which he never published due to his death in WWII. As a matter of fact, RIC III and RSC II (when concerned the Antonines) provide information that is far from complete for almost all types in terms of bust variants, mainly citing only common types with ‘bare head right’ and ‘laureate head right’. In the past decade, the popularity of metal detecting coupled with the development of international internet selling platforms provided new opportunities for discovering new bust variants not listed in RIC and RSC.